Empowerment and satisfaction in a multinational study of routine clinical practice. (4th December 2014) - Clarke, E.; Puschner, B.; Jordan, H.; Williams, P.; Konrad, J.; Kawohl, W.; Bär, A.; Rössler, W.; Del Vecchio, V.; Sampogna, G.; Nagy, M.; Süveges, A.; et al.
<x xml:space="preserve">Abstract</x> Objective Decision‐making between mental health clinicians and patients is under‐researched. We tested whether mental health patients are more satisfied with a decision made (i) using their preferred decision‐making style and (ii) with a clinician with the same decision‐making style preference. Method As part of the CEDAR Study (ISRCTN75841675), a convenience sample of 445 patients with severe mental illness from six European countries were assessed for desired clinical decision‐making style (rated by patients and paired clinicians), decision‐specific experienced style and satisfaction. Results Patients who experienced more involvement in decision‐making than they desired rated higher satisfaction (OR = 2.47, P = 0.005, 95% CI 1.32–4.63). Decisions made with clinicians whose decision‐making style preference was for more active involvement than the patient preference were rated with higher satisfaction (OR = 3.17, P = 0.003, 95% CI 1.48–6.82). Conclusion More active involvement in decision‐making than the patient stated as desired was associated with higher satisfaction. A clinical orientation towards empowering, rather than shared, decision‐making may maximise satisfaction.